2020
DOI: 10.30595/alphamath.v6i2.7866
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesalahan Peserta Didik dalam Menyelesaikan Soal Matematika pada Fungsi Komposisi dan Fungsi Invers

Abstract: In learning mathematics, students often experience mistakes or omissions in solving the questions given both the questions of practice, assignments, tests, and exams. This study aims to determine the student's errors mistakes in solving mathematical problems in the composition and inverse functions in SMA Negeri 1 Maumere. The method used is descriptive qualitative, with X MIPA 4 students' research subjects, amounting to 34 people who were selected based on purposive sampling technique where this subject who g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…The composition of function is one of the concepts delivered in class X of Senior High School (SMA) and is included in the scope of algebra. There are studies that say that there are still many students who make mistakes when studying composition of function concept, both students with high, medium, or low abilities [6]. Referring to the results of the study, there may be forms of errors that have not been identified by previous researchers, especially if the errors are categorized into the AVAEM category (ARITH, VAR, AE, EQS, and MATH).…”
Section: Icmscementioning
confidence: 93%
“…The composition of function is one of the concepts delivered in class X of Senior High School (SMA) and is included in the scope of algebra. There are studies that say that there are still many students who make mistakes when studying composition of function concept, both students with high, medium, or low abilities [6]. Referring to the results of the study, there may be forms of errors that have not been identified by previous researchers, especially if the errors are categorized into the AVAEM category (ARITH, VAR, AE, EQS, and MATH).…”
Section: Icmscementioning
confidence: 93%
“…Secara universal, pembelajaran bertujuan mendidik serta meningkatkan kompetensi partisipan didik. Ilmu yang sangat penting dari ilmu-ilmu yang lain Salah satunya merupakan matematika, yang ialah aspek utama dari disiplin akademik serta memainkan kedudukan berarti dalam pembelajaran [1]. Tidak peduli bagaimana zaman berkembang, matematika tetap menjadi bagian penting dari kehidupan sehari-hari.…”
Section: Pendahuluanunclassified
“…Menurut (Wahyuddin, 2016) ada beberapa faktor yang harus dimiliki siswa agar memperoleh hasil belajar yang baik yaitu kemampuan dalam menyelesaikan soal meliputi: kemampuan menuliskan aspek yang diketahui, kemampuan menuliskan aspek yang ditanyakan, kemampuan membuat model matematika, kemampuan menyelesaikan model matematika, dan kemampuan menjawab pertanyaan soal. Adapun letak kesalahan siswa dalam menyelesaikan soal matematika menurut (Utami, 2017) adalah siswa tidak menyatakan suatu masalah, tidak menentukan apa sebenarnya yang ditanyakan dan harus diselesaikan pada suatu permasalahan, siswa kurang memahami informasi apa yang ada pada permasalahan, siswa kurang cermat dalam menghitung serta kurang memahami konsep. Menurut (Manibuy, 2014) jenis-jenis kesalahan dalam menyelesaikan soal yaitu kesalahan konsep, kesalahan prinsip, dan kesalahan operasi.…”
Section: Pendahuluanunclassified